(untitled) (JAKRA : Jurnal Akuntansi UNWIRA, 2023)
The purpose of this research is to analyze the management of Corporate Social Responsibility (CSR) funds at PT Angkasa Pura I El Tari Kupang Airport. The research method used is descriptive qualitative. The results of the research show that the management CSR funds of PT Angkasa Pura I El Tari Kupang Airport has been carried out well, namely through 1) The planning stage carried out by the Head Office of PT Angkasa Pura I. 2) The implementation stage, namely carrying out the CSR program in a transparent manner and accountable by involving employees, communities, and third parties. They too have a good risk management strategy and funding mechanism. As well as 3) The evaluation stage, namely PT Angkasa Pura I El Tari Kupang Airport conducts an evaluation and monitoring direcly of each implemented program.